PENGARUH APLIKASI PUPUK HAYATI PETROBIO DAN PUPUK NPK MUTIARA 16:16:16 TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max L.) - Fijai Febri Yanto; Siti Zahrah; Sri Mulyani (UIR Press, 2023)
This research aimed to find out the interaction and the main effect between Petrobio biofertilizers and NPK Mutiara 16:16:16 fertilizers on the growth and yield of soybean plants. This research was conducted at the experimental farm of Faculty of Agriculture, Riau Islamic University, Pekanbaru from July to October 2019. The design used in the study was a completely randomized design, consisting of 2 factors. The first factor was the dose of Petrobio's Biofertilizer (P), consisting of 4 levels of treatment namely 0, 3, 6, and 9 g per plot. The second factor was NPK Mutiara 16:16:16 (N) fertilizer dosage, consisting of 4 levels, 0, 10, 20, and 30 g per plot. So that the treatment combinations obtained as 16, consisting of 3 replications with a total of 48 experimental units. The observed parameters were plant height, percentage of pods with a healthy crop, crop weight of seeds, the weight of 100 seeds, harvest index, and further tested BNJ at the level of 5%. The results showed that the interaction of Petrobio Biological fertilizers and NPK Mutiara 16:16:16 fertilizers was significant for the percentage of pithed pods, crop seed weight, and harvest index. Effect of application of Petrobio Biofertilizer dosage, 9 g per plot and NPK Mutiara fertilizer 16:16:16 30 g per plot P3N3. The main effect of Petrobio biological fertilizer was evident in plant height, net assimilation rate, relative growth rate, and weight of 100 seeds. The best treatment is on Petrobio 9 g per fertilizer plot. The main effect of NPK Mutiara 16:16:16 fertilizer was found in all observed parameters. The best NPK Mutiara 16:16:16 fertilizer treatment was at a dose of 30 g per plot.